Pathological Study of Various Types of Pneumonia Prevalent in Sheep of Rajasthan - Shubham; Asopa, Shesh; Mathur, Manisha; Choudhary, Sunita; Arora, Aditya; Joshi, Jay (Indian Journal of Veterinary Sciences and Biotechnology, 2025)
For the present study, 480 tissue specimens of lungs were examined from carcasses of sheep of either sex, irrespective of age groups or breeds subjected to post-mortem examination from October 2023 to March 2024. Out of these, 126 samples representative of gross lesions were processed for subsequent histopathological examination. The overall occurrence of pneumonia in sheep recorded was 53.17 (67/126) %. The occurrence of various types of pneumonia, i.e., bronchopneumonia, interstitial pneumonia, fibrinous pneumonia, haemorrhagic pneumonia, suppurative pneumonia and granulomatous pneumonia were reported as 22.22, 18.25, 2.38, 4.76, 3.17 and 2.38 %, respectively. Bronchpneumonia was reported as the most prevalent, and fibrinous and granulomatous pneumonia least prevalent pneumonia affecting lungs of sheep during the study period.